Antioxidant Activity and Organoleptic Tests on Functional Drinks Made from Soursop Leaves (Annona Muricata) with a Combination of Sappan Wood (Biancaea Sappan) - Eno, Kristina Febrianti; Sintyadewi, Rima; Widnyani, Ida Ayu Putu Ary; Putra, Anak Agung Ngurah Dwi Ariesta Wijaya; Rabani RS, I Gusti Agung Yogi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Functional beverages are popular because they have bioactive compounds that contribute to body health. This study aimed to determine the effect of combining soursop leaves (Annona muricata) and sappan wood (Biancaea sappan) on total phenolic content, flavonoid content, antioxidant activity, and sensory characteristics of a functional beverage. The study employed a Complete Randomized Design (CRD) with one factor consisting of seven treatment combinations, which represented different proportions of soursop leaves and sappan wood. The results showed that the 70% soursop leaves and 30% sappan wood combination (A7B7) produced the highest total phenolic content of 3335.97 mg GAE/100g, the flavonoid content of 2180.35 mg QE/100g, and the lowest IC50 value of 62.02 ppm, indicating strong antioxidant activity. Sensory tests showed that treatment (A1B1) in color parameters showed a significant difference (p<0.05), and treatment (A2B2, A3B3, A4, B4, A5B5, and A6B6) in taste, aroma, texture, and preference parameters did not show a significant difference (p<0.05). The A7B7 combination was identified as the best formulation based on antioxidant activity and panelist preferences.